2011
DOI: 10.1542/peds.2010-2185
|View full text |Cite
|
Sign up to set email alerts
|

Abusive Head Trauma During a Time of Increased Unemployment: A Multicenter Analysis

Abstract: WHAT'S KNOWN ON THIS SUBJECT:Abusive head trauma (AHT) is the leading cause of death from child abuse. Poverty and stress are recognized risk factors for abuse. No studies to date have evaluated whether there is a relationship between the economy and rates of AHT. WHAT THIS STUDY ADDS:Results of this study demonstrate a relationship between an economic recession and the rate of AHT. Given the high morbidity and mortality rates for children with AHT, these results are highly concerning. abstract OBJECTIVE: To e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
4
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 156 publications
(115 citation statements)
references
References 22 publications
4
104
4
3
Order By: Relevance
“…These factors may influence the types and severity of injuries among young children. 5,21,28 Second, adherence to published recommendations may be leading to identification of additional occult injuries. 30,31 Third, the threshold for admitting an injured child into the hospital may have risen over time due to forces in play by insurers to limit inpatient care by definitions of medical necessity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors may influence the types and severity of injuries among young children. 5,21,28 Second, adherence to published recommendations may be leading to identification of additional occult injuries. 30,31 Third, the threshold for admitting an injured child into the hospital may have risen over time due to forces in play by insurers to limit inpatient care by definitions of medical necessity.…”
Section: Discussionmentioning
confidence: 99%
“…4 Berger found a significant increase in incidence of abusive head trauma in a multicenter analysis from 2004 to 2009 among children younger than 5 years. 5 Parks and colleagues, using mortality reports from death certificates between 2003 and 2007, reported decreasing rates of death due to accidental head injury among children aged #5 years but constant rates of death due to abusive head trauma. 6 NCANDS reports death rates due to maltreatment among children aged #3 years of 7.…”
Section: E1796mentioning
confidence: 99%
“…Associations consistent with the family stress model have been found in many other small samples throughout the United States and Europe. Whereas most studies in this literature suffer from omitted variables bias-the effects of economic hardship are identified off differences between families who do and do not experience large economic lossesmore recent studies have reported similar findings using more exogenous measures of economic conditions, e.g., plant closings (3,4), changes in income transfer policy (5,6), and unemployment rates (7,8). We also used more exogenous measures and hypothesized that higher unemployment rates were associated with higher levels of harsh parenting.…”
mentioning
confidence: 89%
“…125,126,127 In relation to fatal child maltreatment, a number of parental characteristics recur, including young maternal age, low level of maternal education, family size, previous abuse, unemployment, parental mental ill-health and substance misuse, domestic violence, and increased parental stress (Panel 5). [128][129] …”
Section: Parental and Wider Social Characteristicsmentioning
confidence: 99%